Predictive factors for changes in remnant stump length during and after the treatment of incompetent truncal saphenous veins using cyanoacrylate. (September 2020) - Lee, Terence SQ; Chan, Sze L; Rathnaweera, Harsha P; Hong, Situ; Chong, Tze T; Tang, Tjun Y
Introduction: The VenaSeal™ Closure System is a non-thermal, non-tumescent venous closure device that employs a cyanoacrylate adhesive to occlude incompetent veins for superficial truncal reflux. The aim was to examine patient, Duplex-defined venous characteristics and treatment-related factors that may predict variances in remnant stump length at the sapheno-femoral and sapheno-popliteal junctions in the peri-procedural period. Methods: A total of 73 patients (87 legs; 85 great saphenous veins; 11 small saphenous veins) of median age 63 years (range 26–86 years) underwent VenaSeal™ Closure System ablation. 44/85 (52%) great saphenous veins were treated with a modified instructions-for-use technique of using double-dose injection of glue (0.3 cc) at initial deposition for great saphenous veins diameters >6 mm. Median great saphenous veins and small saphenous veins lengths ablated were 48.0 cm (range 13–69 cm) and 32.0 cm (range 19–40 cm), respectively. A total of 62/87 (71.3%) legs had CEAP classification 4–6. A completion Duplex scan was performed immediately and 1 week post-procedure to measure remnant stump lengths at the sapheno-femoral and sapheno-popliteal junctions. Multivariate regression modelling was used to look for predictors of remnant stump length. Results: Mean sapheno-femoral and sapheno-popliteal junctions stump lengths immediately post procedure were 33.0 mm (range 0–58 mm) and 27 mm (range 5–33 mm), –17.0 mm and –23.0 mm less than the expected 50-mm baseline length, respectively. At 1 week post-procedure, mean sapheno-femoral and sapheno-popliteal junctions stump lengths were 25.0 mm and 25.0 mm, respectively, the former found to be shorter compared to immediately post-procedure (25 mm vs 33 mm; p < 0.05). Multivariate analysis found larger upper thigh great saphenous veins diameter at sapheno-femoral junction to be predictive of shorter remnant stump lengths immediately post-procedure (<30 mm stump distance). Larger sapheno-femoral junction diameters and pre-existing ischemic heart disease for the sapheno-femoral junction and larger small saphenous veins diameters and age for the sapheno-popliteal junction were predictive of interval shortening of the measured remnant lengths found at the completion of the procedure and 1 week later. Initial double-dosing application of glue was not found to be predictive of shorter stump lengths. Conclusion: In patients undergoing VenaSeal™ Closure System ablation for superficial truncal reflux, larger upper thigh great saphenous veins diameters predicted shorter remnant sapheno-femoral junction stump lengths immediately post-procedure. Comparing stump lengths at one week to immediately after procedure, larger sapheno-femoral junctions and ischemic heart disease predicted shorter stump lengths at the sapheno-femoral junction, while larger small saphenous vein diameters predicted shorter stump lengths at the sapheno-popliteal junction.